(untitled) (Research, Society and Development, 2022)
Aquaculture today represents one of the most critical activities in the production chain of animal protein in Brazil, with an increasing growth rate. Because of this, it is essential to know how the sector is managed and what is its importance for the national economy of this agribusiness segment. This review aimed to describe the importance of fish farming and the management of fisheries agribusiness in Brazil. Therefore, a narrative review was carried out, with studies characterized as qualitative that showed the complexity and details of the information. Thus, the theoretical foundation of this article was divided into two sections. The first was to address some characteristics of Brazilian agribusiness. In the second section, the importance of fisheries agribusiness, and its management for national social and economic development, was addressed. The national fisheries agribusiness, in addition to producing meat from fish farming, offers investment opportunities in the various segments of the production chain, such as the planting of inputs for the manufacture of feed, feed factories, medicines, vaccines, genetic improvement, aquaculture equipment, and implements. In this way, the national fishing agribusiness has great potential to attract national and international investors looking for new business alternatives.